Five‐Year Outcomes in Kidney Transplant Patients Converted From Cyclosporine to Everolimus: The Randomized ZEUS Study. Issue 1 (17th December 2014) - Budde, K.; Lehner, F.; Sommerer, C.; Reinke, P.; Arns, W.; Eisenberger, U.; Wüthrich, R. P.; Mühlfeld, A.; Heller, K.; Porstner, M.; Veit, J.; Paulus, E.‐M.; et al.
<x xml:space="preserve">Abstract</x> ZEUS study was an open‐label, 12‐month, multicenter study in which 300 de novo kidney transplant recipients were randomized to continue receiving cyclosporine (CsA) or convert to everolimus at 4.5 months posttransplant. Five‐year follow‐up data were available for 245/269 patients (91.1%) who completed the core 12‐month study (123 everolimus, 109 CsA). At 5 years, adjusted estimated GFR was 66.2 mL/min/1.73 m2 with everolimus versus 60.9 mL/min/1.73 m2 with CsA; the mean difference was 5.3 mL/min/1.73 m2 in favor of everolimus (95% CI 2.4, 8.3; p < 0.001 [intent‐to‐treat population]). In a post hoc analysis of patients remaining on study drug at 5 years (everolimus 77, CsA 86), mean difference was 8.2 mL/min/1.73 m2 (95% CI 4.3, 12.1; p < 0.001) in favor of everolimus. The cumulative incidence of biopsy‐proven acute rejection postrandomization was 13.6% with everolimus versus 7.5% with CsA (p = 0.095), largely accounted for by grade I rejection (16/21 patients and 7/11 patients, respectively). Postrandomization, graft loss, mortality, serious adverse events and neoplasms were similar in both arms. In conclusion, conversion of kidney transplant patients to everolimus at 4.5 months posttransplant is associated with a significant improvement in renal function that is maintained to at least 5 years. The increase in early mild acute rejection did not affect long‐term graft function.